Control of bronchial asthma and association of factors influencing control of asthma in adult asthmatic patients at the Pulmonary Clinic, Teaching Hospital Jaffna - Sithara, G.S.S.R.; Anuradha, I.J.; Saidha, K.; Anushshiya, S.; Chrishwin, R.; Sivaganesh, S.; Sivakanthan, S. (Faculty of Medicine, University of Jaffna, 2024)
Introduction and objective: People with asthma can have different levels of control over their symptoms: some manage well, some moderately, and others poorly. Doctors monitor how well asthma is controlled by considering daytime and nighttime symptoms, inhaler use, and how much asthma limits activities. Many factors affect asthma control, like age, weight, family history, allergies, smoking, respiratory tract infections, and how waste is handled. The objective of this study is to determine the level of control of bronchial asthma and association of triggers for the control of asthma among adult asthmatic patients at the Pulmonary Clinic, Teaching Hospital Jaffna. Methods: A clinic-based descriptive cross-sectional study was carried out from November 2022 to January 2023 at the Pulmonary Clinic in Teaching Hospital Jaffna by using an interviewer-administered questionnaire. GINA assessment of asthma control in adults was used as a tool. Data were processed and analyzed using SPSS software (Version 22.0). The chi square test was used to determine the association between control of bronchial asthma and socio-demographic factors, duration of bronchial asthma, family history of bronchial asthma, history of allergy for various exposures, sensitization history for different exposures, respiratory tract infections, waste management, and active and passive smoking status. Results: We looked at 356 adult asthma patients and found factors that affect asthma control, like age, weight, family history, specific allergies, past infections, and waste disposal habits. The asthma control levels were categorized as well-controlled (23.9%), moderately controlled (28.1%), and poorly controlled (48%). Older patients and those who are very thin or overweight tended to have worse control. Allergies to pollen, mosquito coils, and pesticides, make control harder, as does exposure to environmental dust (road dust, smoke, and bakery dust). Respiratory tract infections and burning waste also make asthma control worse. Conclusion and recommendations: The study revealed a significant number of adult patients with poorly controlled asthma. To improve asthma control, it is important to live healthily and eat well to maintain a normal weight. Avoiding dust, smoke, and allergens by wearing masks may help. Taking steps to prevent infections is crucial. Also, it is better to recycle waste instead of burning it. These changes can make managing asthma easier.
Keywords: Allergens; Activity limitation; Environmental exposures; Family history; Night time symptoms